3(3x-3)-28=4x-2

Simple and best practice solution for 3(3x-3)-28=4x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-3)-28=4x-2 equation:


Simplifying
3(3x + -3) + -28 = 4x + -2

Reorder the terms:
3(-3 + 3x) + -28 = 4x + -2
(-3 * 3 + 3x * 3) + -28 = 4x + -2
(-9 + 9x) + -28 = 4x + -2

Reorder the terms:
-9 + -28 + 9x = 4x + -2

Combine like terms: -9 + -28 = -37
-37 + 9x = 4x + -2

Reorder the terms:
-37 + 9x = -2 + 4x

Solving
-37 + 9x = -2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-37 + 9x + -4x = -2 + 4x + -4x

Combine like terms: 9x + -4x = 5x
-37 + 5x = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0
-37 + 5x = -2 + 0
-37 + 5x = -2

Add '37' to each side of the equation.
-37 + 37 + 5x = -2 + 37

Combine like terms: -37 + 37 = 0
0 + 5x = -2 + 37
5x = -2 + 37

Combine like terms: -2 + 37 = 35
5x = 35

Divide each side by '5'.
x = 7

Simplifying
x = 7

See similar equations:

| 3/2*(1-4x)^1/2=-30 | | (((3x-1/4)^2))^4 | | 5x-12=10-6x | | FxD=F | | 11/2*31/2*23/4 | | 4=-6+x | | A+C=A | | 6+9=3x | | -30=3r | | 38=7b+10 | | 2(x-1)=10(1-x)+6 | | 3xy+4xy-xy= | | 4x+29=5-8(x+6) | | 25x^2-36=o | | 6(5y-1)=-2y-38 | | 2+4r=5+4r | | X*7-4x=19-2x | | 90=-6(1+8q) | | 1-5m+3m=3 | | -x^3-6x^2+36x+216=0 | | -8-3(w+13)=4(w+11)-7w | | 15=5/6c | | -2(3x+1)-6x+7= | | 3x-2=55 | | 3/4(x-1)=7/4 | | (1-k)X^2-2(1+k)X+3(k+1)=0 | | 3[5x-2]+27=-24 | | 2v^2+11v-5=0 | | C=5/9(50-32) | | 8a-2=3a+5.5 | | 6x-8x+2x= | | 4x+x+(4x+6)+(4x+6)2=166 |

Equations solver categories